Body weight satisfaction: association with weight control practices among Type 2 diabetic patients - Zakaria, Noor Salihah; Lua, Pei Lin; Mamat, Nik Mazlan (Nutrition Society of Malaysia, 2011)
Introduction: The recommendation to lose weight has been the guiding principle in the treatment of type 2 diabetic patients. However, to facilitate this process, it is vital to understand factors associated with personal feelings about body weight and related behaviour. Methods: The objectives of this cross-sectional study were (1) to determine mean BMI and weight of satisfaction and (2) to measure the association between body weight satisfaction vs. sex, BMI, glycaemic control (as measured by Fasting Blood Glucose (FBG), and attempts to lose weight among type 2 diabetic patients. Descriptive statistics and non-parametric tests were employed (SPSS 16). A total of 67 subjects were recruited from Klinik Kesihatan Bandar Kuantan (age = 54.1 ± 8.1 years; female = 62.7%; Malay = 73.1%; overweight/obese = 62.7%) who completed a set of self-administered questionnaires. Results: The mean BMI and weight of satisfaction were 27.9 ± 5.3 kg/m2 and 62.7 ± 10.9kg respectively. A greater proportion of women (65.0%) reported dissatisfaction with their body weight. Patients with higher BMI generally reported greater dissatisfaction with body weight compared to those with lesser BMI (p = 0.090). There was no significant difference in the glycaemic control of patients who were satisfied or dissatisfied with their weight (p = 0.839). There was also no significant association between body weight satisfaction and diet (p = 0.957), physical activity (p = 0.517) or both (p = 0.734). Conclusion: This study implies that body weight satisfaction alone is not a strong factor that may drive type 2 diabetic patients to control their body weight.